Evaluating the substantivity of silver diamine fluoride in a dentin model - Brian Minavi; Adam Youssefi; Ryan Quock; Ariadne Letra; Renato Silva; Timothy C. Kirkpatrick; Gena Tribble; Ransome van derHoeven (Wiley, 2021)
Abstract Objectives The goal of endodontic therapy is to prevent apical periodontitis. This is achieved by biomechanical preparation, microbial control using endodontic irrigants, and complete obturation of the canal space. In order to prevent possible post‐obturation complications and for an added antimicrobial effect, substantivity is a desired characteristic of endodontic irrigants. Currently the most commonly used endodontic irrigant that produces an antibacterial substantivity effect is chlorohexidine (CHX). Silver diamine fluoride (SDF) is a topically applied agent for managing dental caries and has shown to stop caries lesion progression. The objective of this study was to compare the antimicrobial substantivity effect of 3.8% SDF against other commonly used endodontic irrigants such as 2% CHX and 6.25% Sodium hypochlorite (NaOCl). Material and methods Using a diffusion disc assay we determined the antimicrobial activities of 38%, 3.8%, 0.38%, and 0.038% of SDF against the bacterium Enterococcus faecalis OG1RF. Subsequently, we compared the levels of colonization of E. faecalis by scanning electron microscopy (SEM) at 1.5‐ and 3‐week time intervals on dentin pretreated with 3.8% SDF, 6.25% NaOCl, 2% CHX or sterile phosphate buffered saline (PBS). Results The diffusion disc assay demonstrated that 38% and 3.8% of SDF inhibited the growth of E. faecalis. Moreover, the substantivity of 3.8% SDF (p < 0.01) was comparable to 2% CHX (p < 0.01) and it is significantly greater than 6.25% of NaOCl compared to the PBS treated samples after 1.5 and 3 weeks of incubation. Conclusions In this study, we demonstrate that SDF possesses antimicrobial properties against the opportunistic pathogen E. faecalis. Moreover, using a dentin model we show the substantivity of 3.8% SDF is significantly greater than 6.25% NaOCl, but is comparable to 2% CHX.